CAR NK-92 cells targeting DLL3 kill effectively small cell lung cancer cells in vitro and in vivo. Issue 4 (28th January 2022) - Liu, Manting; Huang, Wensou; Guo, Yongjian; Zhou, Yubo; Zhi, Cheng; Chen, Jingwu; Li, Junping; He, Jinping; Lian, Hui; Zhou, Jingwen; Ye, Xiaodie; Hu, Yuling; et al.
Abstract: Small cell lung cancer (SCLC) is characterized by a high relapse rate, drug tolerance, and limited treatment choices. Chimeric antigen receptor (CAR)-modified NK cells represent a promising immunotherapeutic modality for cancer treatment. However, their potential applications have not been explored in SCLC. Delta-like ligand 3 (DLL3) has been reported to be overexpressed in SCLC and may be a rational target for CAR NK immunotherapy. In this study, we developed DLL3-specific NK-92 cells and explored their potential in the treatment of SCLC. A coculture of DLL3 + SCLC cell lines with DLL3-CAR NK-92 cells exhibited significant in vitro cytotoxicity and cytokine production. DLL3-CAR NK-92 cells induced tumor regression in an H446-derived pulmonary metastasis tumor model under a good safety threshold. The potent antitumor activities of DLL3-CAR NK-92 cells were observed in subcutaneous tumor models of SCLC. Moreover, obvious tumor-infiltrated DLL3-CAR NK-92 cells were detected in DLL3 + SCLC xenografts. These findings indicate that DLL3-CAR NK-92 cells might be a potential strategy for the treatment of SCLC. Graphical Abstract: DLL3-CAR NK-92 cells showed significant anti-tumor effect on small cell lung cancer both in vitro and in vivo.